PROSPECTS FOR THE DEVELOPMENT OF REMOTE BANKING SERVICES IN THE CONTEXT OF BANKING TRANSFORMATION - Jabborov Bahriddin Rashidovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In this article, the scientific and theoretical views on the importance of remote banking services in banking activities, the channels for providing them, and the possibilities for their further expansion were studied. The state of development of remote banking services in the practice of commercial banks of Uzbekistan was analyzed based on collected statistical data.